THE IMPORTANCE OF MARKETING RESEARCH FOR THE COMPETATIVENESS OF SMALL ENTERPRISESS IN REPUBLIC OF MACEDONIA - Petkovska Mirchevska, Tatjana; Daniloska, Natasha; Hadzi Naumova-Mihajlovska, Katerina; Filkov, German (Institute of Economics - Skopje, 2017)
Meeting the global needs of consumers by applying a marketing concept is one of the key factors for competitive success and is a basis for positioning of enterprises, regardless of the nature of their activity or size. All enterprisess need a marketing concept, regardless of their size and business activity. Even though small enterprises, in terms of their size and flexibility have many specifics and differences, marketing is a universal concept in terms of fullfilling numberous factors of competitiveness. To achieve sustainable growth and competitive position, small enterprises should be oriented towards exploring the factors of the immediate and more wider environment and should identify approaches and strategies for market positioning accoding to the needs and demands of consumers. In this paper, a theoretical and emperical review has been made on the application of marketing research in small enterprises in Republic of Macedonia, in relation to several factors of their competitiveness. The analysis of the current situation of the use of marketing research, in terms of improving competitiveness, shows that small enterprises in the country do not sufficiently apply the marketing concept and marketing research for improving their competitiveness and their successfull positioning in the global market.
Keywords: marketing research, competitiveness, SMS’s, Republic of Macedonia